Sorption of Rare-Earth Elements and Ac on UTEVA Resin in Different Acid Solutions. Issue 4 (7th June 2017) - Marinov, G.; Marinova, A.; Milanova, M.; Happel, S.; Lebedev, N. A.; Drokhlyansky, Abigail; Mirzayev, Nijat; Karaivanov, D. V.; Filosofov, D. V.
ABSTRACT: The distribution of some rare-earth elements (REEs) on Uranium and TEtraValent Actinides (UTEVA) resin was determined from different concentrations of inorganic (HCl, HNO3, HClO4, HPF6 ) and one organic acid – CCl3 COOH. Low sorption of all REEs in the range of 1 M–5 M HNO3 was observed. In more concentrated HNO3, a rapid increase of the distribution coefficients (Kd ) was noticed with an increase in the atomic number of the lanthanides as well as in Y and Sc. The system UTEVA–CCl3 COOH showed a higher selectivity for Eu(III). Chromatographic elution profiles were checked in order to confirm the obtained Kd values.